Mustahik's Participation Model in the Productive Zakat Fund Distribution Program - Haerul Jamal; Turasih Turasih (Prosperity: Journal of Society and Empowerment, 2022)
Since the issuance of Law No. 23 of 2011 concerning Zakat Governance, zakat has become one of the instruments of state development. however, in practice, the process of distributing zakat funds is still dominated by a distribution model that is consumptive and very minimally involves mustahik as the beneficiary of the program in the process. Mustahik is only used as an object in the process of distributing zakat funds, even though community participation is the spirit of community empowerment. As a result, zakat has not been able to solve the problem of poverty and improve the standard of living of mustahik. The process of preparing this paper uses the literature study method and explains that there are two models of community participation in the productive zakat fund distribution program, namely the community participation model based on technical assistance and self-help approaches. These two participation models can be a reference to formulate a program for distributing productive zakat funds so that productive zakat funds can have more impact on mustahik.